21st century skills, individual competences, personal capabilities and mind-sets related to sustainability: a management and education perspective - Wim Lambrechts (The Central European Review of Economics and Management (CEREM), 2019)
Aim: This editorial article provides a general introduction into the topic of this special issue. It highlights the attention given to, and the differences in interpretations of, 21st century skills, individual competences, personal capabilities and mind-sets related to sustainability, specifically in management and education contexts. Furthermore, the article gives an overview of the articles included in this special issue.~Design/Research methods: Recent developments in the field are presented, based on a literature review. Differences in interpretations between management and education perspectives, as well as differences~ and similarities in conceptualisations of these constructs are discussed.~Findings: The article describes current issues that are being discussed in the debate around 21st century skills, individual competences, personal capabilities and mind-sets related to sustainability. Although different concepts are presented in the literature, they also have basic assumptions and characteristics in common, mainly the combined (holistic) approach of skills, competences, attitudes and values. However, the discussion has become blurred due to mixing interpretations of business context and education context.~Originality/value of the article: The main value of this introductory article of the special issue, is that it outlines similarities and differences in interpretations of 21st century skills, individual competences, personal capabilities and mind-sets related to sustainability.
Keywords: I20; I23; J24; Q01; Q56; 330; 21st century skills; individual sustainability competences; capabilities; mind-sets; higher education for sustainable development; sustainable management